Prevalence of Wound Complications Due to Diabetes in Patients Undergoing Abdominal Surgery (Medical Forum Monthly, 2021)
Objective: The main objective of the study is to analyze the wound complications due to diabetes in patients undergoing abdominal surgery.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Anatomy Department, Swat Medical College, Swat during March 2020 to August 2020.Materials and Methods: A wide range of routine stomach medical procedures aside from those done in crisis were remembered for the investigation.Results: The data was collected from 120 patients. The mean age of the complete example was 55.5 years. Most of the example was male (51.1%), non-smokers (95.6%) and didn't have hypertension (67.8%). The normal span after conclusion of diabetes mellitus was 6.1 (SD 6.3) a long time.Conclusion: It is concluded that it is difficult to treat the wound complication in diabetic patients. It can be difficult to differentiate local soft tissue infection and inflammation from osteomyelitis.